Biodiesel from Waste Cooking Oil using Activate Carbon as Adsorbent and Synthesis of Triaacetin using Nitric Acid as Catalyst - Novi Nuraeni; Yenny Febriani Yun; Dewi Meliati Agustini (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
Waste cooking oil is a waste of frying oil that is containing high free fatty acids (% FFA). The waste could be made to be useful as biodiesel and triacetin. Biodiesel was produced by addition of 4 % (oil weight) activated carbon with stirring for 1hour at 90-100 oC then transesterification of waste cooking oil. The results showed the yield of the biodiesel was 95.28 % with flash point 179oC, water content 0.13 %, acid value 0.59, total glycerol 0.03 %, and the by-product glycerol 10.05 % (oil weight). Triacetin was synthesized by esterification of the glycerol with acetic acid with mol ratio 1 : 7 at 120oC used nitric acid catalyst (5 % glycerol weight). The results showed that the conversion of acetic acid was low, 24.05 %. That showed nitric acid could be a good catalyst in the esterification of triacetin.